BRD4 directs hematopoietic stem cell development and modulates macrophage inflammatory responses. (6th March 2019) - Dey, Anup; Yang, Wenjing; Gegonne, Anne; Nishiyama, Akira; Pan, Richard; Yagi, Ryoji; Grinberg, Alex; Finkelman, Fred D; Pfeifer, Karl; Zhu, Jinfang; Singer, Dinah; Zhu, Jun; et al.
Abstract: BRD4 is a BET family protein that binds acetylated histones and regulates transcription. BET/BRD4 inhibitors block blood cancer growth and inflammation and serve as a new therapeutic strategy. However, the biological role of BRD4 in normal hematopoiesis and inflammation is not fully understood. Analysis of Brd4 conditional knockout (KO) mice showed that BRD4 is required for hematopoietic stem cell expansion and progenitor development. Nevertheless, BRD4 played limited roles in macrophage development and inflammatory response to LPS. ChIP‐seq analysis showed that despite its limited importance, BRD4 broadly occupied the macrophage genome and participated in super‐enhancer (SE) formation. Although BRD4 is critical for SE formation in cancer, BRD4 was not required for macrophage SEs, as KO macrophages created alternate, BRD4‐less SEs that compensated BRD4 loss. This and additional mechanisms led to the retention of inflammatory responses in macrophages. Our results illustrate a context‐dependent role of BRD4 and plasticity of epigenetic regulation. Synopsis: New conditional mouse knockout models of the BET family protein BRD4, involved in transcriptional control in hematopoietic cancers, reveal its differential requirement in normal hematopoiesis and inflammation. BRD4 is required for development and proliferation of mouse hematopoietic stem cells. BRD4 is dispensable for macrophage differentiation and inflammatory response. BRD4 broadly occupies genic and intergenic regions of transcribed genes in both unstimulated and LPS‐stimulated macrophages. Brd4 deletion is associated with increased NF‐κB occupancy and increase of other BET proteins. Abstract : New mouse models and genomic analyses reveal context‐dependent roles for BRD4 during normal hematopoiesis and inflammation.